Contribution of Red Blood Cells to the Saturable Mechanism of Heparin Clearance - Young, Edward; Hirsh, Jack (Thrombosis and Haemostasis, 1990)
The pattern of clearance of intravenously administered heparin suggests the participation of a saturable mechanism which has been ascribed to heparin binding to the endothelium. Another potential site of heparin binding which may contribute to the saturable mechanism is the red blood cells. We have examined this possibility using unfractionated heparin together with a chemically-modified low affinity heparin labelled with tritium as tracer. Unfractionated heparin and the radioactive tracer were added to pooled plasma at a fixed concentration. The heparinized plasma was mixed with red cells to reconstitute whole blood. After centrifugation, the radioactivity, APTT, anti-Xa and anti-Ila activities were measured in the resultant plasmas. No evidence of significant binding to red cells could be detected even when the hematocrits of the reconstituted whole blood were increased. These results are at variance with those of a previously published report. We conclude that red cell binding does not contribute to the saturable mechanism of heparin clearance.